Are MMP3, MMP8 and TIMP2 gene variants associated with anterior cruciate ligament rupture susceptibility?. Issue 7 (July 2019) - Lulińska-Kuklik, Ewelina; Rahim, Masouda; Moska, Waldemar; Maculewicz, Ewelina; Kaczmarczyk, Mariusz; Maciejewska-Skrendo, Agnieszka; Ficek, Krzysztof; Cieszczyk, Pawel; September, Alison V.; Sawczuk, Marek
Abstract: Objectives: Anterior cruciate ligament rupture (ACLR) is a common and severe knee injury which typically occurs as a result of sports participation, primarily via a non-contact mechanism. A number of extrinsic and intrinsic risk factors, including genetics, have been identified thus far. Matrix metalloproteinases (MMPs) and tissue inhibitors of metalloproteases (TIMPs) play a crucial role in extracellular matrix remodeling of ligaments and therefore the genes encoding MMPs and TIMPs are plausible candidates for investigation with ACL rupture risk. Design: A case-control genetic association study was conducted on 229 (158 male) individuals with surgically diagnosed primary ACLR, ruptured through non-contact mechanisms and 192 (107 male) apparently healthy participants (CON) without any history of ACLR. All participants were physically active, unrelated, self-reported Caucasians. Methods: All participants were genotyped for four single nucleotide polymorphisms (SNP): MMP3 (rs591058C/T, rs679620 G/A), MMP8 (rs11225395C/T), and TIMP2 (rs4789932 G/A) using standard PCR assays. Gene-gene interactions were inferred. Single-locus association analysis was conducted using the Chi-square test. SNP-SNP interaction effects were analysed using multifactor dimensionality reduction (MDR) method. Results: Genotype frequencies did not significantly differ between cases and controls, however, the MMP3 rs679620 G and rs591058C alleles were significantly overrepresented in cases compared to controls (p = 0.021, OR = 1.38, 95% CI: 1.05–1.81). Conclusions: These results support the hypothesis that genetic variation within MMP3 contributes to inter-individual susceptibility to non-contact ACLR. However, these results need to be explored further in larger, independent sample sets.